Transcription of the Medieval Birch-Bark Manuscript from Turku - Kinnunen, Jussi; Harjula, Janne (The Society for Medieval Archaeology in Finland, 2026)
The paper focuses on the paleographical analysis of the first medieval birch-bark manuscript found in Finland. The object was C14-dated to the 14th century, and named after its finding spot as ‘the birch-bark letter of the Turku Cathedral Square’. Firstly, the birch-bark document was scanned using microscope photography. Secondly, digital microphotographs were combined, and the contrasts on the script were amplified with digital image processing. The transcription of the whole script of the birch-bark manuscript of the Turku Cathedral Square written with gothic minuscules can be read seu his qui ri[???] lybeus duxit kirrkunum auari quibus. The text and message of the birch-bark manuscript from Turku is an extremely rare example of medieval non-formal language use in medieval Finland as it enlightens the thoughts of a medieval common citizen. The meticulous documentation and paleographical analysis of the find carried out leaves the opportunity for alternative interpretations and translations of the text in the future.